Reconstructing a Chicano/a Literary Heritage Hispanic Colonial Literature of the Southwest - Herrera-Sobek, María (University of Arizona Press, 1993)
Early literary works written in Spanish in what is today the American Southwest have been largely excluded from the corpus of American literature, yet these documents are the literary antecedents of contemporary Chicano and Chicana writing.This collection of essays establishes the importance of this literary heritage through a critical examination of key texts produced in the Southwest from 1542 to 1848. Drawing on research in the archives of Southwestern libraries and applying contemporary literary theoretical constructs to these centuries-old manuscripts, the authors-all noted scholars in Chicano literature-demonstrate that these works should be recognized as an integral part of American literature. CONTENTS Introduction: Reconstructing a Chicano/a Literary Heritage, by María Herrera-Sobek Part I: Critical Reconstruction Shipwrecked in the Seas of Signification: Cabeza de Vaca's La Relación and Chicano Literature, by Juan Bruce-Novoa Discontinuous Continuities: Remapping the Terrain of Spanish Colonial Narrative, by Genaro Padilla A Franciscan Mission Manual: The Discourse of Power and Social Organization, by Tino Villanueva The Politics of Theater in Colonial New Mexico: Drama and the Rhetoric of Conquest, by Ramón Gutiérrez The Comedia de Adán y Eva and Language Acquisition: A Lacanian Hermeneutics of a New Mexican Shepherds' Play, by María Herrera-Sobek Part II: Sources of Reconstruction Poetic Discourse in Pérez de Villagrá's Historia de la Nueva México, by Luis Leal Fray Gerónimo Boscana's Chinigchinich: An Early California Text in Search of a Context, by Francisco A. Lomelí "¿Y Dónde Estaban las Mujeres?": In Pursuit of an Hispana Literary and Historical Heritage in Colonial New Mexico, 1580-1840, by Tey Diana Rebolledo Entre Cíbolos Criado: Images of Native Americans in the Popular Culture of Colonial New Mexico, by Enrique Lamadrid